Assessing fatigue in childhood cancer survivors: Psychometric properties of the Checklist Individual Strength and the Short Fatigue Questionnaire––a DCCSS LATER study. (24th December 2021) - Penson, Adriaan; Walraven, Iris; Bronkhorst, Ewald; Grootenhuis, Martha A.; Tissing, Wim J. E.; van der Pal, Helena J. H.; de Vries, Andrica C. H.; van den Heuvel‐Eibrink, Marry M.; Neggers, Sebastian; Versluys, Birgitta A. B.; Louwerens, Marloes; Pluijm, Saskia M. F.; et al.
Abstract: Background: Fatigue is often reported by patients with childhood cancer both during and after cancer treatment. Several instruments to measure fatigue exist, although none are specifically validated for use in childhood cancer survivors (CCS). The aim of the current study was to present norm values and psychometric properties of the Checklist Individual Strength (CIS) and Short Fatigue Questionnaire (SFQ) in a nationwide cohort of CCS. Methods: In total, 2073 participants were included from the Dutch Childhood Cancer Survivor Study (DCCSS) LATER cohort. Normative data, construct validity, structural validity, and internal consistency were calculated for the CIS and SFQ. In addition, reliability and a cutoff score to indicate severe fatigue were determined for the SFQ. Results: Correlations between CIS/SFQ and vitality measures asking about fatigue were high (>0.8). Correlations between CIS/SFQ and measures of different constructs (sleep, depressive emotions, and role functioning emotional) were moderate (0.4–0.6). Confirmatory factor analysis resulted in a four‐factor solution for the CIS and a one‐factor solution for the SFQ with Cronbach's alpha for each (sub)scale showing good to excellent values (>0.8). Test–retest reliability of the SFQ was adequate (Pearson's correlation = 0.88; ICC = 0.946; weighted Cohen's kappa item scores ranged 0.31–0.50) and a cut‐off score of 18 showed good sensitivity and specificity scores (92.6% and 91.3%, respectively). Conclusion: The current study shows that the SFQ is a good instrument to screen for severe fatigue in CCS. The CIS can be used as a tool to assess the multiple fatigue dimensions in CCS. Abstract : Several instruments to measure fatigue exist, although none are specifically validated for use in childhood cancer survivors (CCS). The current study shows that the SFQ is a good instrument to screen for severe fatigue in CCS and that the CIS can be used as a tool to assess the multiple fatigue dimensions in CCS.